Unveiling the user acceptance of Moodle in German language education - Permana, Pepen; Permatawati, Irma; Khoerudin, Ending; Muthmainah, Nur; Oktapiani, Widia (Intelektual Pustaka Media Utama, 2025)
Motivated by the need to understand the role of digital tools such as Moodle in foreign language learning, this study explores the acceptance and use of Moodle by students in the German Language Education Study Program at Universitas Pendidikan Indonesia (UPI). Using a mixed-method approach, we examined students’ acceptance of Virtuelles Klassenzimmer (VKZ), a Moodle-based e-learning platform, within the technology acceptance model (TAM) framework. 246 students were surveyed using a structured questionnaire encompassing both quantitative and qualitative components. Quantitative data aligned with TAM constructs (perceived usefulness (PU), perceived ease of use (PEOU), attitude toward using (ATU), and behavioral intention (BI)) were analyzed using mean and standard deviation (SD) values. Qualitative data from open-ended questions on VKZ’s advantages and disadvantages were examined using thematic analysis. Results indicate that students generally responded positively to using Moodle in German classrooms, appreciating its benefits in enhancing language learning. However, concerns about Moodle’s usability and mobile compatibility were also identified. This study proposes improvements in Moodle’s design and functionality to address these issues, emphasizing its potential in language education. Future research should explore these findings in diverse educational contexts to enhance the application of digital tools in language learning.